Deglaciation of the Central Nain-Okak Bay Section of Labrador - Johnson, Jr., J. Peter (ARCTIC, 1969)
A complete glaciation of the highest peaks in this region, indicated by erratics on the top, is tenatively correlated with the Torngat glaciation, and a subsequent advance from interior Labrador, during which the highest peaks were nunataks, to the Koroksoak glaciation. The last deglaciation was basically a recession accompanying thinning of the interior Labrador ice sheet. In the Nain-Okak Bay region it occurred in four steps. Low lying areas were still occupied by isolated masses of stagnant ice when the eustatic sea-level rise began. The events leading to complete deglaciation are reconstructed mainly from the distribution of moraines, kame terraces and other ice contact and fluvioglacial features. In the absence of accurate C-14 dating, the chronology suggested is relative rather than absolute. Déglaciation de la section centrale Nain-baie d'Okak, au Labrador. Sur les plus hauts sommets de la section Nain-baie d'Okak du Labrador, des erratiques glaciaires indiquent qu'à un certain moment, toute la région était entièrement recouverte de glace. On relie provisoirement cette glaciation à celle de Torngat. Une réavancée subséquente, venue de l'intérieur, au cours de laquelle les plus hauts sommets ont constitué des nunataks, semblerait correspondre à la glaciation de Koroksoak, car les systèmes morainiques des niveaux inférieurs sont apparemment ceux de la glaciation de Saglek et ses différentes phases. La déglaciation finale a consisté surtout en une récession accompagnée d'un amincissement de l'inlandsis intérieur, tandis qu'au début du relèvement eustatique du niveau de la mer, des masses de glace stagnante occupaient encore les régions les plus basses.